Urban [vertical] agriculture: prospects of a food sovereignty alternative in Johannesburg - Agrizzi, Nikita (My University, 2017)
The aim of this study was to explore stakeholder’s perceptions of whether urban agriculture is a viable alternative food system in the city. The food system in South Africa is locked into a corporate controlled monopoly that has led to the contradictory coexistence of both waste and hunger. While corporations are able to make money off necessities, we see an everwidening gap between the ‘haves’ and the ‘have nots’. This presents an urgent need to redress food insecurity through an alternative food system rooted in food sovereignty – reconnecting people to nature, forming social relations around our food, and producing nutritious food that feeds all equally and equitably. While urban agriculture has grabbed the attention of scholars in recent decades, this research explored what challenges the development and implementation of urban agriculture as an alternative food system from the perception of key stakeholder’s. Urban agriculture has been advocated for by food sovereignty activists as a means to attain this alternative food system, therefore the study sought to investigate the extent to which this is viable by uncovering the socio-economic, socio-political and ecological viability of urban agriculture including urban vertical agriculture. Data was collected by means of an in-depth semi-structured interview. The data was collected for a period of 5 months, from June 2016 to November 2016. In total twelve interviews were conducted with at least one stakeholder from a variety of sectors: The Gauteng Department of Agriculture and Rural Development, Urban farmers, Market Agents from the Joburg Market, Non-governmental Organisations (NGOs), the Commercial sector, Agricultural colleges, City planners/municipalities and academics. Interviews were on average an hour long, and were transcribed and reflected upon. The key findings of this study are that there is a large presence of food gardens in Johannesburg, and stakeholder’s hold these gardens to high esteem in being used as a safetynet for the most vulnerable population. As a result, these gardens are not being geared towards creating an alternative food system, as they are regarded with little value outside being a safety-net. For the working-class affordability takes priority over sustainability as sustainable produce is often more expensive making it less accessible to the majority of South Africans. Therefore, price is a limitation to sustainable practices, and unless a significant number of people of all income levels have access to local and sustainably grown food, sustainable agriculture will not be able to make a significant impact on the environment and our health to make a difference. Furthermore, this research found that there are insufficient change agents trying to form an alternative food system. Based on the thinking of most participants who are in many ways linked to what is happening in the field, they are not thinking of a solution to food security in the form of an alternative food system, but rather thinking of increasing production in the hope that it will reach those who need it most. Thus based on the findings of this research, the way in which urban agriculture is being structured it will form part of the capitalist economy and do little do challenge and redress the political economy of food in South Africa. There is a pressing need for a greater movement that works together and educates the masses for substantial changes to be made in the future.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters in Development Studies
Keywords: Agriculture--Economic aspects--South Africa; Urban agriculture; Land use